Fabrication of bead-on-string polyacrylonitrile nanofibrous air filters with superior filtration efficiency and ultralow pressure drop - Huang, Jeanne Jinhui (2021)
The presence of ultrafine particle matter (PM) in air is one of the most hazardous environmental issues because of their severe threat to human health. Design and development of cost-effective and energy-efficient air filters to remove the PM by facile methods are highly demanded. Electrospun nanofibrous membranes have been explored for PM filtrations as they can achieve high removal efficiencies due to their ultrafine nanofibers. However, their enhanced particle removal efficiencies are at the cost of high pressure drops. In this work, porous bead-on-string filters with nanobeads along the nanofiber axis have been successfully fabricated by optimizing the polyacrylonitrile (PAN) concentration of electrospun dopes and ambient humidity condition during the electrospinning process. The combined effects of polymer concentration and humidity condition could achieve an unbalanced status between the repulsive and constrictive forces along the jets from the spinneret in the electrospinning process, which generated a filter with a desirable bead-on-string morphology. The nanobeads are able to reduce the packing density and alleviate the pressure drop through the filter while the ultrafine nanofibers guarantee the PM removal efficiency. Besides, the effects of nanofiber diameter, airflow rate and nanobead density on the filtration efficiency and pressure drop of NaCl solid and Paraffin oil aerosols with an average diameter of 300 nm have been investigated systematically. With the assistance of bead-on-string construction, the pristine PAN filter can easily achieve an excellent efficiency above 99% with a low pressure drop of 27 Pa at an airflow rate of 4.2 cm/s. This work suggests that transformation of electrospun filters from a nanofibrous structure to a bead-on-string morphology via the adjustments of polymer concentration and ambient humidity is sufficient to generate filter mediums with excellent efficiency and low airflow resistance for air filtration applications, which is also facile to be scaled up as no special equipment and costly chemicals are required.